New species and new records of Mesonemoura (Plecoptera: Nemouridae) from China - Li, Mengyu; Yang, Ding; Li, Weihai (Zootaxa, 2024)
A new species of the genus Mesonemoura, M. yadonga sp. nov. (Plecoptera: Nemouridae) is described from Xizang of southwestern China. The new species is compared to similar congeners. Two additional species are recorded for the first time from China. The hitherto unknown female of M. falcata (Kimmins, 1950) is described.